Anaemia of chronic disease in gastroenterology outpatients – scan not scope!. (13th March 2011) - Hazeldine, S; Chelvaratnam, U; Thomas, P D; Pugh, S
Abstract : Introduction: Patients with anaemia of unknown origin are often referred for gastroenterological investigations. This is commonly due to an anaemia of chronic disease (ACD) as a consequence of an underlying inflammatory or neoplastic process. Referring clinicians are often unfamiliar with the biochemical indices that help distinguish this from iron deficiency anaemia (IDA) and there can be difficulty in establishing a cause in mixed IDA and ACD states. Patients are often frail and unfit for endoscopy. The optimal method for investigating ACD has not been established. We aimed to study a group of patients with ACD referred to gastroenterology outpatients using contrast CT scanning of the chest, abdomen and pelvis as the primary diagnostic tool. Methods: 53 consecutive patients with ACD referred to gastroenterology outpatients between 1/1/09 and 30/6/10 were identified from a database. All patients met the following criteria: Hb <13 g/dL men and <12 g/dL women, ferritin >30, B12 and folate normal. Patients were assessed clinically by one of 2 clinicians and if deemed fit and had no apparent cause for the anaemia underwent a contrast CT of chest, abdomen and pelvis. Results: The mean age was 76 (range 53–93), mean Hb 10.1 (6–12.8), MCV 90.3, ferritin 233 (31–1346). 35 patients underwent whole body contrast CT scanning. 18 patients did not undergo CT on the advice of the clinician due to frailty (n = 4), GFR<60 (n = 7), inflammatory conditions thought to explain the ACD. Of the 35 CT examinations, 9 (26%) were normal. 8 (23%) revealed benign non-significant pathology (NSP). 12 (34%) patients had a diagnosis of cancer, none of which were of luminal GI origin (3 renal cell, 3 lung, 1 bladder, 1 adrenal, 1 hepatoma, 1 pancreatic cancer with metastases, 1 prostate cancer with metastases, 1 metastases with unknown primary). 6 (17%) patients had significant 'benign' findings, for example, cavitating lung lesion, pulmonary haemorrhage due to vasculitis. Comparison of the 17 patients with normal/NSP and the 18 patients with malignancy or significant benign pathology revealed no significant difference in age (p = 0.5), ferritin (p = 0.1), MCV (p = 0.96), CRP (p = 0.05). Conclusion: The diagnostic yield for whole body contrast CT in ACD is high with 51% patients having either malignant or significant benign pathology. One third of those assessed had malignancy, most of which was non-gastrointestinal in origin. This compares with an approximate 10% diagnosis of malignancy in patients presenting with IDA. Haematological causes were comparatively rare. Serum indices such as Hb, ferritin and CRP levels could not distinguish between those patients with normal/benign pathology and those with malignancy/significant benign disease. Whole body CT should be the preferred investigation in patients presenting with ACD for which no obvious cause is evident.